Recomposing Identities: Prehistory And Human Origins From Jan Christiaan Smuts To Thabo Mbeki - (:unkn) unknown (My University, 2019)
The development of prehistoric archaeology in South Africa represents an instance of colonial archaeology as a research setting, in which an interest in the material past is imported and implemented in the context of settlement and domination. The utility of such a discipline is amply demonstrated in the second quarter of the 20th century. Encouraged by empirical discoveries, by dedicated scientists, and by Field Marshal J.C. Smuts, prehistory proved twice useful: to position South Africa and the southern hemisphere as a global actor, and to provide an equidistant unifying ground for the infighting Boer and Briton communities of the Union. The 'cradle of humankind', promoted in those interwar years on both scientific and economic grounds, provides a link to post-apartheid times. As former President Thabo Mbeki expressed on numerous occasions, the deep past of humanity carries historical but also moral meaning, as a cornerstone of the African renaissance-then as now, the prehistoric past can serve as a means for recomposing identities in the present.
Keywords: African Research